Heartstopper. Volume 1 - Oseman, Alice (Oseman, Alice. Heartstopper., 2020)
One day in class, shy Charlie Spring sits by rugby player Nick Nelson. A friendship follows, and Charlie develops feelings for Nick, which makes him sad--he is sure he will never have a chance. What he doesn't know is that Nick is questioning his own feelings.